The Convergence of Some Products in the Adams Spectral Sequence - Wang, Yuyu; Wang, Jianbo (Mathematica Scandinavica, 2015)
In this paper, we will use the family of homotopy elements $ζ_n\inπ_*S$, represented by $h_0b_n\in \operatorname{Ext}_A^{3,p^{n+1} q+q}(\mathsf{Z}_p, \mathsf{Z}_p)$ in the Adams spectral sequence, to detect a $ζ_n$-related family $γ_{s+3}β_2ζ_{n-1}$ in $π_*S$. Our main methods are the Adams spectral sequence and the May spectral sequence, here prime $p≥ 7$, $n>3$, $q=2(p-1)$.